The Effect of The Use of Android Applications on Increasing the Motivation of SMA Students on Plantae Materials - Sepany Ade Rowista Damanik (International Journal Labs, 2023)
The use of android applications as Plantae teaching materials is currently a trend in science education research. This study aims to determine the effect of using android applications as teaching materials in increasing the motivation of high school students on Plantae material. The research design used is posttest-pretest-control group design. The subject of the study was SMAN 1 Panombeian Panei, precisely in Simalungun Regency, which consisted of one experimental class and one control class. Collecting data using a learning motivation questionnaire with a Likert. The data obtained were analyzed for the gain to determine the increase in learning motivation of high school students. The results showed that the use of android applications as Plantae teaching materials can have a significant effect on increasing high school students' learning motivation